An experience sampling study of worry and rumination in psychosis. Issue 8 (June 2014) - Hartley, S.; Haddock, G.; Vasconcelos e Sa, D.; Emsley, R.; Barrowclough, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Increasing research effort is being dedicated to investigating the links between emotional processes and psychosis, despite the traditional demarcation between the two. Particular focus has alighted upon two specific anxious and depressive processes, worry and rumination, given the potential for links with aspects of delusions and auditory hallucinations. This study rigorously explored the nature of these links in the context of the daily life of people currently experiencing psychosis. Method Experience sampling methodology (ESM) was used to assess the momentary links between worry and rumination on the one hand, and persecutory delusional ideation and auditory hallucinations on the other. Twenty-seven participants completed the 6-day experience sampling period, which required repeated self-reports on thought processes and experiences. Multilevel modelling was used to examine the links within the clustered data. Results We found that antecedent worry and rumination predicted delusional and hallucinatory experience, and the distress they elicited. Using interaction terms, we have shown that the links with momentary symptom severity were moderated by participants' trait beliefs about worry/rumination, such that they were reduced when negative beliefs about worry/rumination (meta-cognitions) were high. Conclusions The current findings offer an ecologically valid insight into the influence of worry and rumination on the experience of psychotic symptoms, and highlight possible avenues for future intervention strategies.